Systematic Management Approaches in Digital Platform Implementation: A Qualitative Analysis of Merdeka Mengajar Platform for Elementary Teacher Professional Development - Usman, Usman; Suwandari, Lilis (Papanda Publisher, 2025)
The implementation of digital platforms for teacher professional development has become increasingly critical in contemporary educational contexts, yet limited research examines systematic implementation processes in resource-constrained elementary schools. This study investigated the implementation of the Merdeka Mengajar Platform (PMM) in improving teacher academic capacity through self-training at SDN Sindangsari and SDN Caringin Nunggal. A qualitative multi-site case study approach was employed, involving 12 participants including classroom teachers, principals, and school supervisors. Data were collected through semi-structured interviews, participatory observation, and document analysis over six months. Systematic qualitative analysis revealed that both schools successfully implemented PMM through coordinated management functions including planning, organizing, directing, coordinating, controlling, and evaluating. Key findings demonstrated measurable improvements in teacher competencies, particularly in diagnostic assessment and differentiated learning approaches. Implementation challenges included technological infrastructure limitations, varied digital literacy levels, and time constraints, which were addressed through adaptive solutions such as extended access hours, technical training programs, and peer support mechanisms. The study revealed that systematic organizational approaches proved more influential than technological capabilities in determining platform effectiveness. School leadership played a critical moderating role through sustained coaching and motivational support. The research contributes empirical evidence to educational management literature by demonstrating how systematic management functions facilitate successful digital platform integration in elementary education contexts. Findings suggest that effective PMM implementation requires comprehensive organizational commitment, adaptive leadership, and sustained support mechanisms addressing both technical and pedagogical dimensions. The study provides practical insights for educational institutions implementing digital professional development platforms while addressing contextual constraints in developing educational environments.